(untitled) (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2021)
The Spanish Society of Pediatrics (SEP) defines nephrotic syndrome (NS) as one of the most frequent primary glomerulopathies in pediatric patients characterized by urine protein greater than 40 mg/m2/h, hypoalbuminemia less than 2.5 g/dL and edema, accompanied by other symptoms such as hypercholesterolemia, hypertension, hematuria, and oliguria. Being edema the main clinical characteristic, NS groups a series of glomerulopathies where there are lesions in the podocytes, altering the selective permeability of the glomerular filtration barrier causing the passage of proteins. Objective: To establish the clinical and epidemiological characteristics in patients diagnosed with nephrotic syndrome in the Children’s Hospital "Dr. Francisco de Icaza Bustamante". Method: The present research work is a retrospective, cross-sectional, non-experimental quantitative approach with a sample of 362 patients diagnosed with NS in the Children’s Hospital "Dr. Francisco de Icaza Bustamante" in the period of time 2017 - 2020.